Toxicity effect of Ricinus communis methanolic extracts against Bactrocera cucurbitae (Diptera: Tephritidae) - Sadia Manzoor; Rasheed Akbar; Afaq Hussain; Amjad Ali; Brekhna Faheem; Maid Zaman; Abid Farid; Ijaz Hussain; Imtiaz Ali Khan; Kahkashan Perveen (ORCID: (Plant Protection Science)
Bactrocera cucurbitae, commonly known as the melon fruit fly, stands as a formidable threat to global agriculture, particularly in the cultivation of cucurbitaceous crops. The adaptability, high reproductive capacity, and broad host range of B. cucurbitae make it a persistent challenge for growers worldwide. Conventional control methods, often reliant on chemical pesticides, pose environmental and ecological concerns, necessitating the exploration of alternative strategies for sustainable pest management. Invasive plants often exert deleterious effects on ecosystems, and the castor bean plant, Ricinus communis, is no exception. To explore the efficacy of R. communis, a methanol extract was tested to find the toxicity effect against B. cucurbitae. In this study, different bioactive compounds were isolated from R. communis. The crude extract of R. communis was subjected to fractionating using different organic solvents in an increasing order of polarity, where the fraction indicating maximum activity was then taken for the isolation of the bioactive compounds using various chromatographic and spectroscopic techniques such as column chromatography, thin layer chromatography (TLC), gas chromatography-mass spectrometry (GC-MS). The concentrations of R. communis extracts at 0.5, 1.0, 1.5 and 2% methanol were used. Pure methanol was used as the control. The experimental conditions were maintained at 28 + 20 ºC and 65 + 5% relative humidity. The experiment was laid out in a complete randomised design having five replications. A probit analysis was used to find the LC50 and LC90. The results showed that, as the concentration of the plant extracts increases, the mortalities of B. cucurbitae also increased. After a 72 h exposure period, the crude extracts exhibited the lowest LC50 at 0.30% and LC90 at 0.60%. This study investigates the potential of methanolic extracts derived from various parts of R. communis to serve as a biopesticide against B. cucurbitae which can be easily available, economically feasible, socially acceptable and environmentally friendly.